La Industria Azucarera - Lanusse, Roberto Alejandro (Buenos Aires)
Signatura: E 33/08 Otro título: Revista Azucarera
Existencia: 1925- 31(381); 1928- 33(413); 1971- 76(919)
Keywords: Argentina; Industria Azucarera; Azucar